Perception of Stakeholders on the Impacts of Religious Counselling on National Safety - Abdullateef Shittu; Taiye Hassan Ahmed (Bisma The Journal of Counseling, 2023)
An insecure country cannot develop effectively, whatever its laudable development goals and objectives. The most challenging aspect of divided societies is that they face special obstacles in maintaining peace caused by various factors, one of which is religion and belief. The study aims to analyze the perception of stakeholders on the impact of religious counselling on national safety. A descriptive research design of survey type was used. The sample size was 50 male and female respondents which consisted of 10 religious leaders, 5 counselling professionals and 35 security personnel. Religious Counselling National Safety Questionnaire (RCNSQ) was the data collection instrument.  The analysis of Variance (ANOVA) statistical tool was used for testing the hypothesis at 0.05 level of significance. The finding showed that there is no significant difference in the perception of the stakeholders on the impact of religious counselling on national safety (p.> 0.05). The study concluded that the professional counsellors, religious leaders and security personnel perceived that religious counselling has positive impacts on national safety. Based on the conclusion, the study recommended that the government should employ professional religious counsellors in schools and security agencies. This would assist in dealing with the people who are traumatized by the negative happenings that are threatening national safety.